Renal Replacement Therapy and Barriers to Choice: Using a Mixed Methods Approach to Explore the Patient’s Perspective - Jennette, MSW, Caroline; Derebail, MD, Vimal; Baldwin, LCSW, Judy; Cameron, LCSW, Sandra (The Journal of Nephrology Social Work, 2010)
Alternatives to in-center hemodialysis as treatment for end-stage renal disease have been shown to increase patient quality of life, decrease co-morbidities and decrease financial strain on both the patient and the health care system. Focus groups (n = 6 groups with 47 participants) and survey data (n = 113) were used to ascertain perceived barriers and facilitators to alternative therapies and psychosocial and educational issues that may affect a patients’ choice of modality among patients utilizing in-center dialysis, home dialysis and renal transplantation. Fear emerged as a predominant theme, both at diagnosis and when choosing a modality. Distrust of the medical system, denial and patient experiences with previous modalities were seen as barriers to care. Results imply that interventions addressing fear and providing more comprehensive pre-dialysis education may decrease barriers.